Ultrasensitive Mach-Zehnder Interferometric Temperature Sensor Based on Liquid-Filled D-Shaped Fiber Cavity - Hui Zhang; Shecheng Gao; Yunhan Luo; Zhenshi Chen; Songsong Xiong; Lei Wan; Xincheng Huang; Bingsen Huang; Yuanhua Feng; Miao He; Weiping Liu; Zhe Chen; et al. (Sensors, 2018)
A liquid-filled D-shaped fiber (DF) cavity serving as an in-fiber Mach–Zehnder interferometer (MZI) has been proposed and experimentally demonstrated for temperature sensing with ultrahigh sensitivity. The miniature MZI is constructed by splicing a segment of DF between two single-mode fibers (SMFs) to form a microcavity (MC) for filling and replacement of various refractive index (RI) liquids. By adjusting the effective RI difference between the DF and MC (the two interference arms), experimental and calculated results indicate that the interference spectra show different degrees of temperature dependence. As the effective RI of the liquid-filled MC approaches that of the DF, temperature sensitivity up to −84.72 nm/°C with a linear correlation coefficient of 0.9953 has been experimentally achieved for a device with the MC length of 456 μm, filled with liquid RI of 1.482. Apart from ultrahigh sensitivity, the proposed MCMZI device possesses additional advantages of its miniature size and simple configuration; these features make it promising and competitive in various temperature sensing applications, such as consumer electronics, biological treatments, and medical diagnosis.